The Influence of Key Opinion Leaders on Consumer Purchasing Behavior on Social Media - Jasmine Sekar Arum (Asosiasi Ahli Administrasi Indonesia, 2023)
The purpose of this study was to determine the influence of KOL on consumer purchasing behavior among vocational students. Respondents came from Politeknik Negeri Bandung, Indonesia, students who have social media. The research method used is a quantitative method with a quantitative descriptive approach. The data collection method was carried out by distributing questionnaires via Google Form, and the sample in this study was 144 respondents. The validity and reliability test results show that the research is valid and reliable. Simple regression analysis produces a coefficient of 25.6%, indicating that KOL has an effect on consumer purchasing behavior. The results prove that KOL has a significant influence on consumer purchasing behavior.